Perkembangan dan Isu Krusial dalam Undang-Undang KUHP - Yenny Fitri Z; Zuhdi Arman; Pipin Wahyudi; Putri Nilam Sari (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2023)
At the beginning of 2023, the government finally passed Law Number 1 in 2023 on the Criminal Code (KUHP Law). This law is a new step towards criminal law reform following the values of the Indonesian nation. In legal adages, the presumption iures de iure principle is known, which means that everyone is assumed to know the law. People's ignorance of the law is not an excuse to exempt them from being guilty. Therefore, it is necessary to conduct socialization by various groups on the birth of a legal product, one of which is carried out by Lecturers and students of the Faculty of Law. This socialization occurred in Jorong Sianau Indah, Nagari Sungayang, Tanah Datar Regency. The socialization was held on Friday, September 8, 2023. As a result of this socialization, the community began to get clear and correct information about forming a legal product and how to interpret the correct article formulation.